Pendidikan Islam dalam Pengembangan Adversity Quotient Mahasiswa Fakultas Tarbiyah di Perguruan Tinggi Berbasis Pesantren - Moh. Fakhrul Asnawi (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study examines the role of Islamic education in developing the Adversity Quotient (AQ) of students at the Faculty of Tarbiyah, Universitas Al-Hikmah Indonesia (UAI) Binangun, a boarding-school-based higher education institution in Tuban, East Java. In the era of disruption, prospective educators face complex psychological and academic pressures, requiring strong mental resilience. This qualitative research employs a case study approach. Data were collected through in-depth interviews with the dean and lecturers, participant observation of online learning and social projects, and documentation of academic archives. Data analysis followed the interactive model of Miles, Huberman, and Saldaña. The results indicate that the integration of Islamic values such as sabr, tawakkul, istiqamah, and amanah with the pesantren riyadhah tradition significantly strengthens the four dimensions of AQ: Control, Ownership, Reach, and Endurance (CORE). The design of Islamic education learning through the stages of assimilation, accommodation, and balance based on online platforms and social project activities serves as the upstream source for developing students' adversity intelligence. This study concludes that the boarding-school-based higher education model provides a comparative advantage in producing prospective educators who are not only cognitively competent but also excel in spiritual and mental resilience